2005
DOI: 10.1016/j.compstruct.2004.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Rate dependent constitutive modelling of laminated FRP composites degraded by fire

Abstract: A constitutive theory is proposed for FRP laminated composite materials that is designed to account for both temperature and strain rate dependent response, such as would occur during, and after, exposure to the elevated temperatures due to fire. The theory is physically based, and in particular, is based on a kinematical framework fixed on the fabric laminates; full accounting of laminate reorientation and anisotropic response is thus achieved. The theory is numerically implemented and FEM analysis of compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recent analytical and experimental works (e.g. Asaro and Dao, 1997;Asaro et al, 1999Asaro et al, , 2005Asaro et al, , 2009bBirman et al, 2006;Dao and Asaro 1999;Feih et al, 2007aFeih et al, , 2007bFeih et al, , 2010Gu and Asaro, 2005;Ramroth et al, 2006) treated thermal softening as well as the phase transition in chemical decomposition as the major influences on the mechanical properties of polymer matrix composites under fire damage. In the analytical simulation using the ratedependent micromechanical constitutive model (Ramroth et al, 2006) and the experimental evaluation Dao and Asaro 1999), it was found that rate dependence and plastic deformation were unlikely to be the mechanisms for failure of structure-size panels under considered fire protection time.…”
Section: Temperature Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent analytical and experimental works (e.g. Asaro and Dao, 1997;Asaro et al, 1999Asaro et al, , 2005Asaro et al, , 2009bBirman et al, 2006;Dao and Asaro 1999;Feih et al, 2007aFeih et al, , 2007bFeih et al, , 2010Gu and Asaro, 2005;Ramroth et al, 2006) treated thermal softening as well as the phase transition in chemical decomposition as the major influences on the mechanical properties of polymer matrix composites under fire damage. In the analytical simulation using the ratedependent micromechanical constitutive model (Ramroth et al, 2006) and the experimental evaluation Dao and Asaro 1999), it was found that rate dependence and plastic deformation were unlikely to be the mechanisms for failure of structure-size panels under considered fire protection time.…”
Section: Temperature Distributionmentioning
confidence: 98%
“…Finally, the constitutive relation between the rate of Piola-Kirchhoff stress S and the rate of Green-Lagrange strain E is given by: 4.42] where L and X a are related to the deformation gradient, the current stress, the slip system and the elasticity tensor. An example to simulate micro-buckling progress using the constitutive model was given in Asaro et al (2005). The specimen geometry was taken to be stubby so that the global buckling (Euler buckling) was precluded.…”
Section: Plastic Micro-bucklingmentioning
confidence: 99%
“…In particular, exposure to elevated temperatures is known to cause the degradation of the polymer, and consequently of the composite as well, when exposed to temperature levels at, or above, the glass transition temperature [ 5 ]. Composite materials are known to degrade through ablation and charring which causes loss of material and deterioration in performance because of thermal aging, even prior to material loss [ 6 ]. Notwithstanding the higher temperature resistance of reinforcing fibers, polymer matrix composites are susceptible to thermo-oxidative degradation at temperatures between 100 °C and 350 °C, with effects increasing in the vicinity of, and above, the glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Asaro et al [ 6 ] proposed a constitutive theory based on a kinematical framework fixed on the fabric laminated composite materials to account for both temperature and strain rate‐dependent response during and after exposure to the elevated temperatures or fire. Gibson et al [ 7 ] modeled a loaded composite woven glass/polyester laminate under one‐sided heat flux of 75 kW/m 2 and predicted that in the case of compressive collapse, ply failures are beginning at the cold side and not at the hot face.…”
Section: Introductionmentioning
confidence: 99%